A finite element-based analysis approach for computing the remaining strength of the pressure equipment with a local thin area defect. (January 2022) - Lu, Yen-Ju; Wang, Chen-Hua
Highlight: Using FEM, a procedure is established to evaluate the remaining strength of Level 3 LTA defects. An executive program is proposed to calculate the plastic collapse load (PCL). A method is proposed to establish the true defect model. Allow the submodel to retain the complete characteristics of LTA (such as uneven thickness profile), while considering the impact of equipment on LTA, thus maintaining the analysis accuracy while saving time during analysis. Abstract: Upon facing a pressure equipment with a structure defect and the subsequent question as to if the equipment is qualified for continuous operation, the answer often resorts to enough strength. However, strength of a pressure equipment is never defined clearly. In API 579, in order for a pressure equipment with a local thin area (LTA) defect to be accepted for continuing use in operation, the remaining strength factor (RSF) of the equipment must exceed 0.9. RSF is defined as the ratio of the plastic collapse load (PCL) of equipment with defect to that of the equipment without any damage. Hence, accurate evaluation of the plastic collapse load is of utter importance to judge fitness of the equipment. In this research, a finite element (FEM) based methodology has been devised to obtain an accurate estimation of the plastic collapse load. What needs to be established first is a finite element model for the whole, undamaged vessel as the main model and the other is the surrounding region encompassing the LTA defect as the sub-model. Pressure loadings are incrementally and continuously applied to the main model through load steps until the model can no longer sustain, and the plastic collapse load is the maximum load that a structure can safely carry. The cut boundary data from the main model is then passed on to the sub-model, and calculation is resumed with the same load steps until the PCL of the LTA is obtained. Then RSF is determined as the PCL of the vessel with an LTA to that of the original, damage free vessel. API 579 and ASME FFS propose the use of RSF as an indicator for assessing fitness of an equipment. Concept-wise, the term RSF is not sophisticated and sometimes is treated as rough guidance for assessing the remaining strength of a structure. However, the same concept must be treated differently as it is applied to determine whether the defect is allowed and the remaining life is needed, which ought to be a finite element-based approach. In this research, it is achieved through: 1. Representing the defect in the form of a submodel consisting of SOLIDS element in order to process the area of varied thicknesses, and. 2. Computing the plastic collapse load for both the undamaged finite element model of SHELL elements and the submodel of SOLIDS elements simultaneously.